Faktor-Faktor yang Mempengaruhi Niat Bidan dalam Pencegahan Paparan Infeksi Hiv dan Aids di Kabupaten Sidoarjo: Factors Affecting Midwives' Intentions in Preventing Exposure to Hiv and Aids Infections in Sidoarjo Regency - Christy, Januar Dwi (Universitas Muhammadiyah Sidoarjo, 2018)
Midwife is one group of health workers who have a high risk of contracting HIV infection, therefore Prevention of Infection people needed by health personnel for midwives. This study aims to find out how the intention of midwives in preventing infection in the district sidoarjoa. This research is explanatory study with cross sectional approach. This study used sample of 85 midwives in Sidoarjo District. The results of the results obtained midwife did not inted to prevent HIV / AIDS infection by 62.4%. Variables related to midwife intentions are knowledge of infection prevention, attitudes toward infection prevention, supporting facilities in infection prevention, whereas for the duration of the work there is a rather insignificant relation.